FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN OTOMOTIF DAN KOMPONEN - ALVIN WILLIAM PRATAMA; STEVEN YAP (E-Jurnal Manajemen Trisakti School of Management (TSM), 2021)
This study aims to analyze the influence of independent commissioners, net profit margins, return on equity, PBV, and PER on stock returns. In this study 13 automotive companies and components were used as populations listed on the Indonesia Stock Exchange in the period 2005 to 2016 and the selection of data was selected based on purposive sampling techniques. The data analysis method used is multiple linear regression and hypothesis testing. The results of the study using the t test show that partially independent commissioners, net profit margins, PBV, and PER do not affect stock returns, and return on equity partially has a positive influence on stock returns. When there is an increase in income for shareholders, investors will certainly buy the shares because an investor will expect more returns on his investment. Companies that have increased income will be chosen by investors because they are considered to be able to provide more return on shares that have been purchased.